Modification of Nano-Clay and Preparation of Polylactic Acid Nanocomposite - Sedaghat, Soheila; Khosravi, Morteza; Mehrabzadeh, Mahmood (Asian Journal of Chemistry, 2012)
Nanoclays are widely used in preparation of polymer clay nanocomposites. The key to the performance of nanocomposites is the quality of dispersion of the nano-clays particles and the interfacial interaction between the matrix and the reinforced phase. Optimization of these properties requires various special and complicated treatments. Alkyl ammonium salts and alkyl amines are used as intercalates for the nano-clay preparation. Poly(lactic acid)/organo-clay nanocomposites were prepared by in situ polymerization technique. The samples were prepared and the effect of modifiers on the structure of polylactic acid nanocomposite samples were studied by using differential scanning calorimeter (DSC) and wide angle X-ray diffraction (XRD).